The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/ctr.12842
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bacterial colonization on graft success after total pancreatectomy with autologous islet transplantation: considerations for early definitive surgical intervention

Abstract: Objective The purpose of this study was to determine whether bacterial contamination of islets affects graft success after total pancreatectomy with islet autotransplantation (TPIAT). Background Factors associated with insulin independence after TPIAT are inconclusive. Although bacterial contamination does not preclude transplantation, the impact of bacterial contamination on graft success is unknown. Methods Patients who received TPIAT at the University of Virginia between January 2007 and January 2016 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In the present study, the rate of posttransplant infectious complications, excluding islet infusion‐related complications such as bleeding, portal vein thrombosis, high portal pressure, and heavy fatty liver, was not significantly different between the two groups, in agreement with previous reports . The rate of posttransplant infectious complications in all patients was 12.9% (14/108), which is quite a bit lower than that in a previous report .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, the rate of posttransplant infectious complications, excluding islet infusion‐related complications such as bleeding, portal vein thrombosis, high portal pressure, and heavy fatty liver, was not significantly different between the two groups, in agreement with previous reports . The rate of posttransplant infectious complications in all patients was 12.9% (14/108), which is quite a bit lower than that in a previous report .…”
Section: Discussionsupporting
confidence: 88%
“…In TPIAT, contamination rates have been reported to range from 39% to 82.2% for pancreas preservation medium and from 22.2% to 64.3% for final islet preparations . Recent studies concluded that microbial contamination does not influence posttransplant complications . For example, Jolissaint et al reported that culture‐positive islets were not related to posttransplant complications but were associated with higher rates of graft failure and poor islet yield in TPIAT .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our findings, in an autotransplantation setting, Jolissaint et al . also found that bacterial contaminants in the final islet preparation were associated with lower islet yield and lower C‐peptide/insulin independence rates in six patients. However, such small number of patients does not allow definitive conclusion and the situation could be different in this latter study because contamination is usually present at a higher load in patient with chronic pancreatitis and pancreatic duct dilatation and obstruction.…”
Section: Discussionmentioning
confidence: 81%
“…In this study, patients with islets suspected to be positive for cultures ( p = 0.01), and with positive gram stains ( p = 0.02), were associated with worse procedure results [ 71 ]. Jolissaint et al [ 72 ] reported worse results among patients with bacterial contaminants in the final islet preparations. In these patients, a significantly lower islet yield and C-peptide level and no insulin independence following surgery were noted.…”
Section: Pancreatic Islet Isolation and Transplantation—technical Aspectsmentioning
confidence: 99%